Adjusting to retirement from sport: narratives of former competitive rhythmic gymnasts - Cavallerio, F.; Wadey, R.; Wagstaff, C. R. D. (Journal of Quantitative Analysis in Sports, 2017)
This study used narrative inquiry to understand the retirement experiences of rhythmic gymnasts. Eight female former competitive gymnasts (M age = 24.5, SD = 8.33) each participated in four life-history interviews. Following dialogical narrative analysis, three narrative typologies were outlined: Entangled Narrative, Going Forward Narrative and Making Sense Narrative. The entangled narrative shows an individual with a monological athletic identity, who is unable to develop a new identity following her retirement to the detriment of her well-being, and wishes to return to being a gymnast. The going-forward narrative describes those former gymnasts who were able to develop multiple identities during their gymnastics career, and are now flourishing in their life post-retirement. The making sense narrative is an emergent narrative, which transcends the previous two narratives. Findings expand narrative research by providing new narrative resources to understand the experience of retirement from gymnastics. These narrative resources might assist gymnasts to expand their narrative repertoire by raising awareness of different narratives available in their culture.